Alterações de fluidos corpóreos na rã Leptodactylus fuscus durante a estivação (Anura, Leptodactylidae). - Abe, Augusto Shinya [UNESP]; Garcia, L. S. (My University, 1990)
The frog, L. fuscus, becomes dormant during the dry season in southeastern Brazil. Plasma and urine were obtained and analyzed for K+, Na+, and osmotic concentrations in active and estivating frogs. Soil water potential from the estivation sites was compared with the osmotic concentrations of the frog. Plasma and urine osmotic concentrations (286.2 +/- 13.8 and 242.3 +/- 17.2 mOsm1(-1), respectively) were higher in the estivating than in active frogs (240.3 +/- 12.8 and 112.7 +/- 15.6 mOsm1(-1); plasma and urine), and the same holds true for plasma K+ content. The Na+ concentration was the same for active and estivating frogs. Soil water potential corresponded to osmotic pressure of 110 mOsm1(-1), showing that L. fuscus may uptake water from the soil during the estivation.
Changes in body fluids of the frog Leptodactylus fuscus during estivation (Anura, Leptodactylidae)
Keywords: adaptation; animal; body fluid; female; frogs and toads; male; osmolarity; physiology; Animal; Anura; Body Fluids; English Abstract; Estivation; Female; Male; Osmolar Concentration; Support, Non-U.S. Gov't